'Thrash yourself Thursday': the production of the 'healthy' child through a fitness-based PE practice - McDermott, Lisa (Sport, education and society, 2012)
Saturating the Canadian landscape are media and health industry discourses representing childhood physical '(in)activity' and 'obesity' as being at 'epidemic' proportion. Increasingly identified as a focus of concern within such representations is the school setting, simultaneously positioned both as a cause of and a key institutional site for redressing these 'pathologies'. Drawing on qualitative research carried out at a Canadian elementary school, this discussion offers a Foucaultian governmental analysis of one school's navigation of this gauntlet of accountability to improve children's health. Specifically, the school-wide fitness-based initiative known as 'Thrash yourself Thursdays', whose objective is the production of 'healthy' students, is examined to understand the power relations enacted through it, and how the target of this practice (i.e. the children) negotiated such efforts to shape their bodily conduct. This in turn, offers a unique contribution to the governmental literature, which is more characterised by attending to discourses and strategies of government rather than how the subjects of such strategies respond to such efforts.